Assess Impact of Lack of Understanding of Primary Health Care Services the Cause of Not Applying to Family Medicine - Alrumaisaa Ahmad Daafi; Wedad Mohammad Alhazmi; Shaima Yahya M Otayf; Ibtihal Hassan Ali Hadi; Wejdan Saddiq Mohammed Hindi; Abduh Hassan Alamodi; Azhar Ahmed Abdu Halawi; Tariq Dohmi Ahmed Mubaraki; Kharifah Mohammad Ibrahim Sherah; Ghadeer Ali Mousa Shibly (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Family physicians, as gatekeepers of medical care, play a vital role in optimizing healthcare utilization and reducing costs. Despite their importance, utilization rates for family health centers (FHCs) remain suboptimal, partly due to insufficient public awareness of the services provided. Understanding patient knowledge and preferences is essential for improving primary healthcare access and outcomes. Methods: This descriptive, cross-sectional study assessed the knowledge of individuals visiting two FHCs about available healthcare services. A structured questionnaire evaluated awareness of services, including preventive care, vaccinations, maternal and infant health, and diagnostic practices. Responses from 165 participants were scored, with a threshold of 70% indicating sufficient knowledge. Statistical analysis explored correlations between knowledge levels and demographic factors, using SPSS version 23.0. Results: The mean correct response rate was 50.9 ± 23.8%, with only 1.2% of participants achieving full awareness. Knowledge levels varied significantly with demographic factors: women, parents, and individuals with chronic illnesses scored higher (P < .001, P = .025, and P = .005, respectively). Frequent visits to FHCs correlated positively with better knowledge (P = .019). Commonly understood services included nursing care (92.7%) and patient referrals (87.9%), while awareness of tuberculosis-related treatments (29.1%) and laboratory testing availability (21.8%) was low. Conclusion: Public knowledge about FHC services is insufficient, limiting effective utilization. Women, parents, and patients with chronic conditions exhibit higher awareness. Targeted educational initiatives and enhanced communication strategies are needed to raise awareness, promote service utilization, and improve primary care outcomes.